2016
DOI: 10.1016/j.apacoust.2015.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic velocity and attenuation coefficient of magnetorheological fluids under electromagnetic fields

Abstract: Magnetorheological fluid (MRF) is a class of smart material whose acoustic properties can be varied rapidly and reversibly by the applied magnetic field. The MRF is proposed to be as actively sound barriers or acoustical metamaterial. This paper presents a theoretical model to study acoustic propagation in MRF under fields based on the Biot-Stoll model.The model considers the coupling interaction between ferro particle and base fluid. This paper investigated the acoustic velocity and attenuation of a commercia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Magnetorheological (MR) suspensions in which magneto-responsive particles are dispersed in media such as silicone oil, mineral oil and hydrocarbons are field-responsive smart materials, demonstrating reversible transformation of their rheological properties in an external magnetic field [ 1 , 2 , 3 , 4 ]. Their rheological behaviors can be finely tuned by adjusting the strength of the external magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetorheological (MR) suspensions in which magneto-responsive particles are dispersed in media such as silicone oil, mineral oil and hydrocarbons are field-responsive smart materials, demonstrating reversible transformation of their rheological properties in an external magnetic field [ 1 , 2 , 3 , 4 ]. Their rheological behaviors can be finely tuned by adjusting the strength of the external magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…MR fluid is a fluid-solid diphase medium, and the parameters for its solid and fluid phases are listed in table 1. Here, the carrier fluid viscosity η, the average diameter of the solid particles D and Moreover, the fluid phase bulk modulus K f and the solid phase bulk modulus K s are selected according to [22].…”
Section: Materials Parameters Of Mr Fluidsmentioning
confidence: 99%
“…Rodríguez-López et al [ 18 , 19 ] analyzed the effects of uniformity, direction, and intensity of the magnetic field on the attenuation of ultrasonic elastic waves in MRF, and the results showed that the sound attenuation increased with an increase in the magnetic intensity until saturation was reached. Shen et al [ 20 ] and Baev et al [ 21 ] investigated the acoustic properties of MRFs in an applied magnetic field. Zielinski et al [ 22 ] and Muhazeli et al [ 23 ] investigated the acoustic absorption properties of foams coped with MRFs under magnetic fields, and found that the sound absorption frequency of the foams could be manipulated by varying the magnetic field.…”
Section: Introductionmentioning
confidence: 99%